ENERGI KINETIK GUNUNG: TELAAH TERHADAP HIKMAH AL-QUR’AN - Abd Haris; Muhyiddin Tahir; Nurfaika Nurfaika (TAFASIR: Journal of Quranic Studies, 2025)
This paper will examine how the context of understanding kinetic energy towards mountains that are invisible to the naked eye, and it must be believed that all forms of beings on this earth are the contribution of Allah Swt. God's involvement with his creatures becomes an understanding and belief that the space of movement of a creature is the will of Allah Swt., so that even mountains have energy, space for movement. Of course, the existence of the creatures of Allah Swt. on this earth is nothing but and cannot be separated from His will. Then, not seeing the movement of the mountain with the naked eye certainly provides a great hikmah for human life. the Qur'an describes how the mountain is involved in the sturdiness of this earth. The type of research used is library research; i.e., a series of businesses or activities that search with the library data collection method. Of course, this article is sourced from the Qur'an, tafsir, books, articles, and later browsing sites related to this theme. The interim result of this study is that the mountain as a being turns out to have the potential for motion hinted at by the Qur'an, even though it is not directly visible to human eyes. By tracing a verse or two related to the movement of mountains, that can be elaborated the view of science that says that kinetic energy is the energy that everybody has because it has speed